Efficacy of Aspirin for Vasculogenic Erectile Dysfunction in Men: A Meta-Analysis of Randomized Control Trials. Issue 5 (October 2020) - Irfan, Muhammad; Ismail, Shaiful Bahari; Noor, Norhayati Mohd; Hussain, Nik Hazlina Nik
One of the major causes of erectile dysfunction (ED) is an endothelial vascular disorder. This meta-analysis is performed to determine the efficacy of aspirin on erectile function in men with vasculogenic ED. For this purpose, CENTRAL, MEDLINE, and reference lists of articles up to November 2019 were searched. Randomized controlled trials (RCTs) were selected that compared aspirin with placebo in men of any ethnicity with vasculogenic ED. A total of 58 trials were retrieved. Finally, two trials of 214 men fulfilled our selection criteria. High selection and detection bias were identified for one trial. The participants showed a significant improvement in erectile function when they took aspirin (mean difference: 5.14, 95% CI [3.89, 6.40], and I 2 = 0%). Although the present meta-analysis suggested that aspirin has a significant effect on the improvement of erectile function, there were limited RCTs available on this topic and doses of aspirin varied. Additional studies are needed to support findings from this meta-analysis. Aspirin needs to be considered by practitioners when prescribing drugs for vasculogenic ED.